Auditory Processing in Fragile X Syndrome - Rotschafer, Sarah E.; Razak, Khaleel A. (Frontiers in Cellular Neuroscience, 2014)
Fragile X syndrome (FXS) is an inherited form of intellectual disability and autism. Among other symptoms, FXS patients demonstrate abnormalities in sensory processing and communication. Clinical, behavioral and electrophysiological studies consistently show auditory hypersensitivity in humans with FXS. Consistent with observations in humans, the Fmr1 KO mouse model of FXS also shows evidence of altered auditory processing and communication deficiencies. A well-known and commonly used phenotype in pre-clinical studies of FXS is audiogenic seizures. In addition, increased acoustic startle is also seen in the Fmr1 KO mice. In vivo electrophysiological recordings indicate hyper-excitable responses, broader frequency tuning and abnormal spectrotemporal processing in primary auditory cortex of Fmr1 KO mice. Thus, auditory hyper-excitability is a robust, reliable and translatable biomarker in Fmr1 KO mice. Abnormal auditory evoked responses have been used as outcome measures to test therapeutics in FXS patients. Given that similarly abnormal responses are present in Fmr1 KO mice suggests that cellular mechanisms can be addressed. Sensory cortical deficits are relatively more tractable from a mechanistic perspective than more complex social behaviors that are typically studied in autism and FXS. The focus of this review is to bring together clinical, functional and structural studies in humans with electrophysiological and behavioral studies in mice to make the case that auditory hypersensitivity provides a unique opportunity to integrate molecular, cellular, circuit level studies with behavioral outcomes in the search for therapeutics for FXS and other autism spectrum disorders.